Cost-effectiveness of rotavirus vaccination in Albania. (7th May 2015) - Ahmeti, Albana; Preza, Iria; Simaku, Artan; Nelaj, Erida; Clark, Andrew David; Felix Garcia, Ana Gabriela; Lara, Carlos; Hoestlandt, Céline; Blau, Julia; Bino, Silvia
Highlights: Rotavirus RV1 and RV5 vaccines would avert 51, 172 outpatient visits and 14, 200 hospitalizations. Each vaccine would avert a total of 27 deaths, 950 DALYs and gain 801 life years. Total cost of RV1 and RV5 vaccines would be US$ 5.77 and US$ 8.66 million, respectively. Introduction of RV1 vaccine would be a highly cost-effective approach in Albania. Abstract: Background: Rotavirus vaccines have been introduced in several European countries but can represent a considerable cost, particularly for countries that do not qualify for any external financial support. This study aimed to evaluate the cost-effectiveness of introducing rotavirus vaccination into Albania's national immunization program and to inform national decision-making by improving national capacity to conduct economic evaluations of new vaccines. Methods: The TRIVAC model was used to assess vaccine impact and cost-effectiveness. The model estimated health and economic outcomes attributed to 10 successive vaccinated birth cohorts (2013–2022) from a government and societal perspective. Epidemiological and economic data used in the model were based on national cost studies, and surveillance data, as well as estimates from the scientific literature. Cost-effectiveness was estimated for both the monovalent (RV1) and pentavalent vaccines (RV5). A multivariate scenario analysis (SA) was performed to evaluate the uncertainty around the incremental cost-effectiveness ratios (ICERs). Results: With 3% discounting of costs and health benefits over the period 2013–2022, rotavirus vaccination in Albania could avert 51, 172 outpatient visits, 14, 200 hospitalizations, 27 deaths, 950 disability-adjusted life-years (DALYs), and gain 801 life-years. When both vaccines were compared to no vaccination, the discounted cost per DALY averted was US$ 2008 for RV1 and US$ 5047 for RV5 from a government perspective. From the societal perspective the values were US$ 517 and US$ 3556, respectively. Conclusion: From both the perspectives, the introduction of rotavirus vaccine to the Albanian immunization schedule is either cost-effective or highly cost-effective for a range of plausible scenarios. In most scenarios, including the base-case scenario, the discounted cost per DALY averted was less than three times the gross domestic product (GDP) per capita. However, rotavirus vaccination was not cost-effective when rotavirus cases and deaths were based on plausible minimum estimates. Introduction of RV1 would yield similar benefits at lower cost.